PELATIHAN PENERAPAN LAPORAN KEUANGAN BERBASIS STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL DAN MENENGAH (SAK EMKM) DAN PEMASARAN DIGITAL PADA UMKM OLAHAN LIMBAH KULIT IKAN DI KOTA CIREBON - Rosnidah, Ida; Fatimah, Siska Ernawati; Hadyati, Siti Nur (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2022)
The production of AJT fish skin crackers, known as "krupuk kulit ikan cucut AJT," is carried out in the city of Cirebon. These crackers are available for tourists who visit the area. While the AJT fish skin crackers already have attractive packaging that appeals to consumers, their marketing is currently limited to the Cirebon area and relies on exhibitions, personal connections, and manual promotions. The product's promotion has not been maximized, thus requiring assistance in digital marketing. Additionally, the AJT fish skin crackers have not been able to create financial reports. The current financial management solely relies on the owner's memory and small notes. Therefore, it is crucial to provide assistance in creating financial reports based on the EMKM accounting standards. The community service assistance conducted by the Faculty of Economics and Business at UGJ, involving a team of professors and students, has been successful. As a result, the owners and employees of the AJT fish skin crackers are now capable of creating financial reports based on EMKM accounting standards and utilizing social media for digital marketing to enhance sales and market share.